Features of morphological and biometric characteristics of reproductive organs of Scots pine trees with different resistance in stands affected by Heterobasidion annosum - Dyshko, V. A.; Ustsky, I. M.; Mikhaylichenko, A. A. (Forestry and Forest Melioration, 2019)
Introduction Scots pine with increased resistance to H. annosum (Fr.) Bref. has massive horizontal roots and an insufficiently developed taproot. It is also characterized by good growth in diameter and depressed growth in height, as well as by a high content of extractives soluble in acetone and chloroform. The complexity of tree diagnostics for disease resistance prompts the search for effective and easily accessible marker traits with a high level of inheritance in the offspring. The aim of the research was to identify relationships between the Scots pine resistance level to damage by H. annosum (Fr.) Bref and the morphological features of cones and seeds. Materials and Methods Scots pine trees with different health status were selected in two stands affected by the annosum root rot. Both stands are located in the territory of the Kharkiv Forest Research Station. The trees which demonstrated viability on the pathological background in the dieback foci were considered ‘resistant’, dying trees were considered ‘affected’. Control was taken in the gaps between the dieback foci. The mensuration parameters of model trees were determined. Then cones were collected and the seeds were obtained. Fruiting was evaluated on a scale of 1 to 5, with 1 representing ‘poor fruit-bearing’ and 5 representing ‘heavy bearing’. Morphological (colour, shape) and biometric (length, width, weight) characteristics of cones, seeds and wings were examined. The variability level of biometric features was determined. Results In both stands the average height of ‘resistant’ trees was greater than that of ‘affected’ (by 3% and 8%). ‘Resistant’ and ‘affected’ trees inside the dieback focus had the lower average heigh as compared to control ones (by 3% and 10% respectively). The average diameter of the ‘resistant’ trees in one of the stands was 15% larger than that of the ‘affected’ trees and in the control. The same indicator in the other stand was less than in the ‘affected’ trees (3%), but it exceeds the control (10%). Variation levels of the diameter of ‘resistant’ trees were increased and those of ‘resistant’ ones and in control were low. ‘Resistant’ trees had better fruiting (3–5 points) than ‘affected’ trees (3–4 points) and in control (1–2 points). In all groups, forms with beige cones predominated (60–71%). Among the ‘resistant’ trees in one of the stands, trees with wide cones made 70%, and in the second stand – 66.7%. Meanwhile, ‘affected’ trees with wide cones were found in one stand only (66.7%). The other stand had the same proportion of the trees with wide and ovoid cones (43%), that of trees with elongated cones was significantly lower (14.3%). Apophyses of ‘resistant’ trees’ cones belonged to f. gibba C. (20%) and f. reflexa C. (80%) types. At the same time, f. plana C. type was often met in ‘affected’ and control trees (43% and 40% respectively). Furthermore, in ‘resistant’ trees, left-handed enantiomorphic forms of cones prevailed (52% and 65% in the stands), and in the ‘affected’ trees – right-handed ones did (60% and 70%). In one of the stands, the seed form in most of the ‘resistant’ and ‘affected’ trees was oval (72 and 70% respectively), and in the other stand it was oblong (100%). The average indices of biometric features of cones, seeds and wings among ‘resistant’ trees were higher than those among ‘affected’ ones (by 9–45%) and control (by 2–24%). Empty seeds were recorded in all trees with no exception (0.15–75%). Conclusions ‘Resistant” trees are characterized by depressed height growth as compared to healthy ones, but they are equal in diameter. Obtained data on the morphological features of cones and seeds (colour, form) showed that there are no significant differences between ‘resistant’ and ‘affected’ trees. The quantitative characteristics of pine reproductive organs are affected by the light and thermal regimes of the gaps, which does not allow using these features as independent criteria when selecting trees resistant to the disease. 3 Figs., 3 Tables, 28 Refs.